Improving Students’ Visual Representation and Conceptual Understanding to Overcome Learning Difficulties in Geometry Using GeoGebra - Sieng, Veasna; Thai, Heng (Universitas Ahmad Dahlan, 2024)
This study investigates the impact of using GeoGebra, a dynamic geometry software, to enhance students’ visual representation and conceptual understanding of Geometry, mainly focusing on vector concepts. The study involved 168 tenth-grade students in Phnom Penh, Cambodia. The research used a quasi-experimental design with control and experimental groups. The experimental group received instruction with GeoGebra, while the control group followed traditional methods. Data from pre-test and post-tests were analysed using descriptive statistics, Mann-Whitney U tests, and N-Gain scores. The results showed that the GeoGebra group had significantly higher N-Gain scores, indicating improved comprehension and problem-solving skills. The study suggests integrating dynamic geometry software into the curriculum to provide a more interactive learning experience and improve learning in Geometry.